Efeitos do método Pilates sobre variáveis de aptidão física em adolescentes. - Welter, Marcos Roberto Torres; Lara, Simone; de Castro, Antônio Adolfo Mattos; de Souza Balk, Rodrigo (Fisioterapia Brasil, 2018)
We aimed to assess the Pilates method over physical fitness variables in teenagers. We divided our sample into two groups, the Pilates group (PG) n=28 who practiced the Pilates method for 21 consecutive weeks (comprehending 2 twice per week with 1 hour duration) and the Control group (CG) n=23, who received lectures on health education. In order to assess participants physical fitness, pre and post intervention, we used the body composition analysis by means of the anthropometry measure, including mass, height, body mass index, waist circumference, waist-hip ratio; as well as the palmar grip strength by means of the manual dynamometry. We found an increase in waist-hip ratio in CG and maintenance of this variable in the PG and an improvement in the palmar grip strength for both groups post intervention. However, the Pilates method practice showed positive effects in the maintenance of central fat measurements in these teenagers; this is important since this is relevant measure for cardio metabolic profile in this subjects. Nevertheless, the effects of the Pilates method on palmar grip strength were not emphasize, possibly due to the executed exercises empathizes central body muscle strength, not peripheral.